Programming Phoenix productive, reliable, fast - McCord, Chris; Tate, Bruce 1965-; Valim, Jose (Pragmatic Bookshelf, 2016)
Don't accept the compromise between fast and beautiful: you can have it all. Phoenix creator Chris McCord, Elixir creator Jose Valim, and award-winning author Bruce Tate walk you through building an application that's fast and reliable. At every step, you'll learn from the Phoenix creators not just what to do, but why. Packed with insider insights, this definitive guide will be your constant companion in your journey from Phoenix novice to expert, as you build the next generation of web applications.
Place of publication from publisher's Web site. - "Version: P1.0 (April 2016).". - Includes bibliographical references. - Online resource; title from title page (Safari, viewed May 25, 2016)
Keywords: Internet programming; Web sites -- Authoring programs; Programmation Internet; Sites Web; Systèmes-auteur; COMPUTERS; General; Web sites; Authoring programs